2010
DOI: 10.3233/jad-2010-091303
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Intake is Associated with a Lower Risk of Cognitive Decline: A Cohort Study from Portugal

Abstract: Abstract. Alzheimer's disease has emerged in recent decades as a major health problem and the role of lifestyles in the modulation of risk has been increasingly recognized. Recent epidemiological studies suggest a protective effect for caffeine intake in dementia. We aimed to quantify the association between caffeine dietary intake and cognitive decline, in a cohort of adults living in Porto. A cohort of 648 subjects aged 65 years was recruited between 1999 . Follow-up evaluation (2005-2008 was carried out on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
94
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 46 publications
2
94
0
2
Order By: Relevance
“…Eskelinen et al (2009) reported a 65 % risk reduction for late-life dementia and AD among drinkers of three to five cups of coffee per day during their middle life, compared with nondrinkers. The caffeine in coffee has been implicated as the active component associated with risk reduction of cognitive decline and dementia among coffee drinkers (Maia and de Mendonca 2002;van Gelder et al 2007), particularly among women (Ritchie et al 2007;Santos et al 2010). However, coffee also contains a variety of other bioavailable and potentially therapeutic phytochemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Eskelinen et al (2009) reported a 65 % risk reduction for late-life dementia and AD among drinkers of three to five cups of coffee per day during their middle life, compared with nondrinkers. The caffeine in coffee has been implicated as the active component associated with risk reduction of cognitive decline and dementia among coffee drinkers (Maia and de Mendonca 2002;van Gelder et al 2007), particularly among women (Ritchie et al 2007;Santos et al 2010). However, coffee also contains a variety of other bioavailable and potentially therapeutic phytochemicals.…”
Section: Introductionmentioning
confidence: 99%
“…The present study is aimed to assess the association between long-term chocolate consumption and cognitive decline, extending a previous analysis of the association between caffeine consumption and cognitive decline [17]. The hypothesis that chocolate could decrease the incidence of cognitive decline by at least 2 points in the score of a widely used cognitive test, the Mini-Mental State Examination (MMSE), was specifically tested in subjects aged 65 and over participating in a cohort study.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial evidence from human epidemiological studies and from experimental studies conducted in animals and cultured cell models indicate that caffeine, when ingested chronically, can decrease Aβ levels, protect against the onset and severity of AD, and in some cases it can reverse behavioral and pathological features of AD [19,21,24,29]. Less clear, however, are the mechanisms by which caffeine exhibits these protective features.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been shown that it can reverse behavioral and pathological features of AD [19,21,22,24,25,[29][30][31][32][33]. Importantly, these protective effects of caffeine are observed using pharmacologically relevant doses [28,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation